Expression of molecular markers of peripheral blood lymphocyte activation before and after eye-preserving treatment for choroidal melanomas of various stages - D.A. Drumi; I.V. Tsukanova; S.I. Poliakova; L.M. Velychko; M.B. Makarova; O.V. Bogdanova (Journal of Ophthalmology)
Purpose: To assess the expression of molecular markers of peripheral blood lymphocyte activation (СD7+, CD54+, CD95+) before and after eye-preserving treatment for Т1 to Т3 choroidal melanoma (CM).